Posthumanism in Hernan Diaz’s In the Distance - Pegah Abedi; Rasool Moradi-Joz (Universitas Sanata Dharma, 2021)
This study is an attempt to shed new light on the potential representation of posthumanism, the posthuman condition in particular, in Hernan Diaz’s tour de force novel entitled “In the Distance.” The main focus of the study is highlighting the inextricable bond between humans and their surroundings in the most anthropocentric trend of posthumanism, and addressing our exploitative way of living and the outcomes of our ill-treatment toward the natural environment, as represented in one of the contemporary fictions, “In the Distance.” We are told that nature is an eternal Eden which was predestined for serving humankind, and will be balanced once it has fulfilled its duty. The novel, however, as evidenced by current environmental issues, makes an effort to warn us about the end of nature and in turn the failure of humanity. In the same context, this study seeks to demonstrate the “In the Distance” novel as one of the main works arguing for post-humanistic principles during and after the colonialization of America, accompanied by modern civilization and technological advancement in the late 19th and early 20th century.